(untitled) (Archaeologia Adriatica, 2020)
This paper present results of the 2011 and 2014 excavations of the Early Neolithic site of Rivine near Stolac. The site is characterized by scarce settlement remains, lack of deposit, almost complete absence of bioarchaeological finds or of a considerable number of other typical Neolithic finds. Another characteristic of this site is very rudimentary pottery in terms of technology with finger impressions as the only decoration. These facts were used as a starting point in the discussion of the character of the site and its relative chronological position, process of Neolithization and role of authochtonous communities in the process in the given area.